2016
DOI: 10.1007/s00109-016-1481-5
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of redox-dependent activation of endothelial Nlrp3 inflammasomes to hyperglycemia-induced endothelial dysfunction

Abstract: Recent studies indicate that inflammasomes serve as intracellular machinery to initiate classical cytokine-mediated inflammatory responses and play a crucial role in the pathogenesis of cardiovascular diseases. However, whether or not the activation of endothelial inflammasomes directly causes cell dysfunction or tissue injury without recruitment of inflammatory cells is unknown. We explored the role of endothelial cell inflammasome activation in mediating tight junction disruption, a hallmark event of endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 59 publications
5
77
0
Order By: Relevance
“…11 Several studies have suggested that ablation of NLRP3 protects endothelial cells from inflammatory damage, leading to attenuation of AS. 12,13 Thus, the NLRP3 inflammasome is proposed to be a key player in the pathogenesis of vascular inflammation. In 2016, Seldin and co-workers 7 showed that TMAO promotes vascular inflammation through signaling of mitogen-activated protein kinase and nuclear factor-jB (NF-jB).…”
mentioning
confidence: 99%
“…11 Several studies have suggested that ablation of NLRP3 protects endothelial cells from inflammatory damage, leading to attenuation of AS. 12,13 Thus, the NLRP3 inflammasome is proposed to be a key player in the pathogenesis of vascular inflammation. In 2016, Seldin and co-workers 7 showed that TMAO promotes vascular inflammation through signaling of mitogen-activated protein kinase and nuclear factor-jB (NF-jB).…”
mentioning
confidence: 99%
“…For example bacterial endotoxin LPS, environmental toxins, high fat diet can contribute to endothelial dysfunction by increasing endothelial permeability and subsequently arterial lipid accumulation in the subendothelial space, thereby initiating atherosclerotic plaque development. Other injurious stimuli like thrombin, histamine and other acute inflammatory mediators can act on endothelium to stimulate opening of their intercellular junctions at the level of adherens and tight junctional complexes [57, 58]. It has been well established that loss of the integrity of inter-endothelial tight junctions contributes to enhanced paracellular endothelial permeability and plasma proteins including albumin and visfatin can impair renal tubular or endothelial tight junctions via activation of Nlrp3 inflammasomes [23, 24, 57, 58].…”
Section: Discussionmentioning
confidence: 99%
“…Other injurious stimuli like thrombin, histamine and other acute inflammatory mediators can act on endothelium to stimulate opening of their intercellular junctions at the level of adherens and tight junctional complexes [57, 58]. It has been well established that loss of the integrity of inter-endothelial tight junctions contributes to enhanced paracellular endothelial permeability and plasma proteins including albumin and visfatin can impair renal tubular or endothelial tight junctions via activation of Nlrp3 inflammasomes [23, 24, 57, 58]. Consistent with these studies, the present study demonstrates that TMAO treatment induces increases in permeability to dextrans in CAECs, via activation of Nlrp3 inflammasomes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As a pattern recognition receptor, NLRP3 is upregulated by stimulation with pathogen-associated molecular patterns (PAMPs) [4], which are recruited by the adapter protein apoptosisassociated speck-like protein containing CARD (ASC), and then converts pro-caspase-1 into cle-caspase-1 (cleaved form) [5]. NLRP3 inflammasome activation transforms proinflammatory cytokines such as interleukin (IL)-1β and IL-18 from their immature "pro" forms to their active forms, which have different effects in different cell types, including phenotypic transformation, cell pyroptosis, and cell membrane permeability [6][7][8]. In macrophages, NLRP3 inflammasome activation is critical in the formation of foam cells and other atherosclerotic lesions in response to proatherogenic stimuli such as cholesterol crystals [9,10].…”
Section: Introductionmentioning
confidence: 99%